Análise socioeconômica e ambiental da extração de caulim no município de Junco do Seridó-PB - Almeida, Alice Costa de (Universidade Federal Rural do Semi-Árido, 2017)
The city Junco do Seridó located in the state of Paraíba, Brazil, contais a great mineral potential which is directly related to a large part of the population directly and indirectly by the extraction of kaolin. This is the economic activity that generates the most income in the city, but this positive scenario does not reflect the reality of local mineral activity, where it is inserted in the face of economic and environmental disorder The study carries out mining approaches to verify the socioeconomic importance of the exploration of the kaolin to the city as well as the environmental impacts caused by it. In view of this, the work was developed in terms of the analysis of kaolin exploration, its production and processing system and their sustainability relations, as well as business retribution for employees and the community. For the accomplishment of this study and the success of the objectives, a quantitative-qualitative methodology was adopted, checking data from bibliographies and related articles, as well as semi-structured interviews with companies, community and employees, followed by on-site visits and dialogues with prospector. As a result, it was found that the existing reserves of kaolin are abundant, with reasonable infrastructure, as well as a strong export power and external market recognition. However, it needs extreme encouragement and organization by the public agencies, constituting a viable solution in the medium term for the development of the city, increasing production and enabling an improvement in life and progress in social relations.
Socioeconomic and environmental analysis of kaolin extraction in the municipality of Junco do Seridó-PB
Keywords: Atividade de mineração; Gestão ambiental; Empresarial; Sustentabilidade; Mining activity; Environmental management; Companies; Sustainability; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA